Analysis of the Utilization of BRI Life Insurance and BPJS Health for Bank BRI KC Jambi City Employees - Haza Hanifa; Dwi Noerjoedianto; Helmi Suryani Nasution (Sean Institute, 2023)
The use of health insurance in Indonesia takes various forms, starting from government health insurance or better known as the National Social Security System (SJSN), in this case the government stipulates Law No. 24 of 2011 concerning the Social Security Administering Body (BPJS). For overall data on active JKN membership coverage in Jambi province as of December 1 2022, there were 3,026,329 participants or 83.08% of the total population of 3,642,763, of which the highest prevalence of participants was in Jambi City with a total participation of 610,498 or the equivalent of 98 .15%. Apart from that, the government also has an institution called a State-Owned Enterprise (BUMN). Bank Rakyat Indonesia is one of the 4 banks affiliated with BUMN. To provide guarantees to each employee, Bank BRI usually guarantees aspects of their health by providing health insurance known as BRI Life. This research is a qualitative research with a case study approach involving 12 informants consisting of BRI Life insurance coordinators, BRI Bank employees, and BRI Bank customers who use BRI Life and BPJS Health insurance. The main techniques in this research are observation and in-depth interviews. The aim of this research is to see the use of health insurance for employees of Bank BRI KC Jambi City in improving health status. This research obtained the results that the use of BRI Life and BPJS Health insurance for BRI Bank employees is not entirely based on the employee's attachment to BRI Bank, employees are free to choose to use company insurance or BPJS Health depending on personal needs.